The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.4322/rbcv.2014.011
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e sobrevivência de larvas do jundiá, Rhamdia quelen, alimentadas com alimento vivo enriquecido e dieta artificial

Abstract: O objetivo do presente estudo foi avaliar a utilização de dieta inerte e do alimento vivo Artemia salina durante a larvicultura do jundiá Rhamdia quelen. As larvas foram alimentadas de acordo com os seguintes tratamentos: náuplios de A. salina (T1), metanáuplios (T2), metanáuplios enriquecidos com ácidos graxos (T3), metanáuplios enriquecidos com ácidos graxos e vitamina C (T4) e dieta artificial (T5). O delineamento foi inteiramente casualizado com cinco tratamentos e quatro repetições (5x4). As larvas foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Studies with silver catfish larvae have been shown that, in order to obtain good growth and better survival rates, the presence of live food during first feeding of the fish is required (DIEMER et al, 2012;BORGES NETO et al, 2013). Thus, considering that the consumption of live organisms (zooplankton) is important for the development of silver catfish post-larvae (BALDISSEROTTO; RADÜNZ NETO, 2004), the use of a BFT system for larviculture of this species of fish may be advantageous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with silver catfish larvae have been shown that, in order to obtain good growth and better survival rates, the presence of live food during first feeding of the fish is required (DIEMER et al, 2012;BORGES NETO et al, 2013). Thus, considering that the consumption of live organisms (zooplankton) is important for the development of silver catfish post-larvae (BALDISSEROTTO; RADÜNZ NETO, 2004), the use of a BFT system for larviculture of this species of fish may be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…It needs to be kept in mind that, although there is a large diversity of microorganisms in BFT waters, the heterotrophic bacteria are the major driving force of the system (DE SCHRYVER et al, 2008), which is not the preferred food of silver catfish larvae. In addition, the use of artificial diets, as the main source of food, has not shown good results of performance and survival in larviculture of this species (PIAIA; RADÜNZ NETO, 1997;BORGES NETO et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For Neotropical fishes there is no information regarding the PNR. According to Lima et al (2017), larvae of R. voulezi are highly specific in the choice of their prey, and therefore the survival and growth in hatchery systems verified by Borges Neto et al (2013) for R. quelen depend on the supply of live prey, because their larvae have difficulties assimilating artificial diets.…”
Section: Discussionmentioning
confidence: 99%